Placental transfusion syndrome in twins - Tuncer, Müyesser (The Turkish Journal of Pediatrics, 1968)
Three sets of twins with placental transfusion syndrome are presented. The importance of this syndrome in perinatal morbidity and mortality is once again emphasized, and the findings in these babies, immediate care after delivery, and terminology are discussed.